2017
DOI: 10.1016/j.neuropharm.2017.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Double dissociation of the anterior and posterior dorsomedial caudate-putamen in the acquisition and expression of associative learning with the nicotine stimulus

Abstract: Tobacco use is the leading cause of preventable deaths worldwide. This habit is not only debilitating to individual users but also to those around them (second-hand smoking). Nicotine is the main addictive component of tobacco products and is a moderate stimulant and a mild reinforcer. Importantly, besides its unconditional effects, nicotine also has conditioned stimulus effects that may contribute to the tenacity of the smoking habit. Because the neurobiological substrates underlying these processes are virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…This 368 correlation indicates that some of the observed variance in behavioral responses throughout the study could be partially explained by the topography of lesion placement and size. Our findings here are consistent with previous studies, in which rats with lesions to p-dmCPu demonstrated deficits in instrumental and operant learning tasks (Corbit et al, 2012;Corbit and Janak, 2010;Hart et al, 2018;Murray et al, 2012;Yin et al, 2005b) 372 and in nicotine discriminated goal-tracking task (Charntikov et al, 2017). For the first time, we demonstrate the 373 involvement of p-dmCPu in associative learning with nicotine stimulus using a paradigm where rats 374 voluntarily self-administer nicotine and where each nicotine infusion is paired with the access to sucrose.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…This 368 correlation indicates that some of the observed variance in behavioral responses throughout the study could be partially explained by the topography of lesion placement and size. Our findings here are consistent with previous studies, in which rats with lesions to p-dmCPu demonstrated deficits in instrumental and operant learning tasks (Corbit et al, 2012;Corbit and Janak, 2010;Hart et al, 2018;Murray et al, 2012;Yin et al, 2005b) 372 and in nicotine discriminated goal-tracking task (Charntikov et al, 2017). For the first time, we demonstrate the 373 involvement of p-dmCPu in associative learning with nicotine stimulus using a paradigm where rats 374 voluntarily self-administer nicotine and where each nicotine infusion is paired with the access to sucrose.…”
supporting
confidence: 89%
“…where transient lesions to p-dmCPu inhibit nicotine evoked responses while transient lesions to a-dmCPu 88 increase goal-tracking rates on saline sessions by disinhibiting responding when nicotine stimulus is not detected (Charntikov et al, 2017). These findings, using the discriminated goal-tracking task used in previous reports, provided an important initial step towards an understanding of behavioral, pharmacological, and neural mechanisms involved in learning with nicotine stimulus.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations